'Tearing itself apart over showpiece projects': Planning-led Local Elections in Aberdeen, 2002–2012. Issue 1 (May 2019) - Walton, William
Abstract : Members of the public wanting to influence the determination of a controversial development proposal will usually rely upon the direct measure of writing to the council to express their opinions. But where the arithmetic of the council is finely balanced, and notwithstanding the restrictions placed on councillors from declaring a definitive position on a live planning application, voters may be able to influence the outcome of the project indirectly via the ballot box. This paper examines the impact which a series of controversial development projects had on the outcome of local elections in Aberdeen between 2002 and 2012. During this period, the city moved from Labour domination to two- and three-way coalition control. In each of the three local elections, two or more of the major parties adopted clear positions on these highly charged proposals. These positions probably impacted upon voting behaviour and certainly influenced post-election coalition-building. Proposals for a new bridge crossing and a new football stadium were narrowly approved, whilst that for a new city centre square was narrowly rejected. In each case, councillors voted predominantly along party lines. The paper demonstrates the significant influence which planning had on the city's electoral politics over the decade.